Voltammetry Detection of Cotinine in Urine Sample - Noor Hasfalina, Razali
Cotinine is a major metabolite of nicotine. Exposure to nicotine is measured by analyzing the cotinine level in the blood, saliva, or urine. Currents methods for determination of cotinine are Gas Chromatography - Mass Spectroscopy (GC-MS) and High Performance Liquid Chromatography (HPLC). In this study, the determination of cotinine in urine sample was performed by Differential Pulse Adsorptive Stripping Analysis (DPAdSV) for the first time .. The urine sample was filtered with filter paper and diluted in 25 ml deionized water. 1 ml sample from the solution was spiked in 9 ml supporting electrolyte, Britton Robinson Buffer pH 7 and determined using optimum parameters such as initial potential, E1 at -1.2, end potential, Et at -1.82, scan rate at 0.30 V/s, deposition potential 0 V, equilibration time 30 seconds and deposition time 0 V. The validation of methodology was described by obtaining regression equation for its linearity by plotting the calibration curve of peak height, ip versus series concentration of cotinine standard solution. A linear graph with regression equation of Y = 1 0.922x + 2.066, correlation coefficient of 0.991, standard deviation of +0.938, sensitivity of 10.922 uA/ppm and limit of detection of 0.258 ppm was obtained. 10 smoker urine samples were analyzed. Eight samples including the non-smoker urine sample showed the presence of cotinine in different concentration level with a range of 0.31 ppm to 29.15 ppm. Cotinine is not detected in the two remaining urine samples.